A Re-examination of Lowry's Hypothesis for Turkish Case - Yakup Kucukkale; Rahmi Yamak (European Regional Science Association (ERSA), 2001)
Lowry's (1966) hypothesis indicates the predominance of in-migration and the relative insignificance of out-migration with regard to the net migration rates. In the literature, there has been a body of studies which attempted to empirically test the Lowry's proposition , following Lowrys study (Alonso, 1971, 1972; Beale, 1969a, 1969b; Cordey-Hayes and Gleave, 1973, 1975; Kriesberg and Vining, 1978; Lansing and Mueller, 1967; Plane Rogerson and Rosen, 1984; Gedik, 1992). One of the previous empirical studies was provided by Gedik (1992%29. Gedik investigated the hypothesis for Turkey during the periods of 1965-70, 1975-80 and 1980-85. Her findings were contrary to the findings for developed countries. Then, Gedik argued that in the future Turkish case will come to resemble the developed countries. The main objective of this study is to re-examine the Lowry's hypothesis and Gedik's argument on the hypothesis for Turkish case during the period of 1985-90. The results of this paper imply that Gedik's argument is not valid for Turkish case, migration patterns do not approximate those estimated for the developed countries. The findings of the paper can be summarized as follows: (1) The correlation coefficient between net migration and out-migration rates was found to be –0.89 for all provinces. For provinces with net in-migration, it was found to be –0.317, but statistically insignificant. It was -0.96 for provinces with net out-migration. (2) The correlation coefficient between net migration and in-migration was 0.89 for provinces with net in-migration and 0.63 for all provinces. (3) The correlation coefficient in- and out-migration rates was –0.21 for all provinces, 0.39 for provinces with net out-migration and 0.13 for provinces with net in-migration but statistically insignificant.
Keywords: 330